Enabling Learning: Language Teaching for Australian Universities - Caruso, Marinella; Fraschini, Nicola; Kinder, John (LCNAU Studies in Languages and Cultures, 2024)
Enabling Learning: Language Teaching for Australian Universities illuminates efforts by tertiary language educators to facilitate the learning of languages at the university level. The educators' endeavours recounted in this volume address a range of specific aspects of the language learning experience or language teaching within tertiary education institutions. The chapters offer an overview of learning approaches and experiences, from the beginner to the advanced level, of different learning environments, from the traditional to online and hybrid, and of different languages, from Indigenous to European to East Asian. This work foregrounds the relevance of improved accessibility to language learning in the university context, presents innovative educational solutions informed by the examination of specific contexts, and asserts the importance of developing intercultural competence.